Proceedings of the 14th Annual ACM Symposium on User Interface Software and Technology 2001
DOI: 10.1145/502348.502357
|View full text |Cite
|
Sign up to set email alerts
|

Parallel bargrams for consumer-based information exploration and choice

Abstract: In this paper we introduce multidimensional visualization and interaction techniques that are an extension to related work in parallel histograms and dynamic querying. Bargrams are, in effect, histograms whose bars have been tipped over and lined up end-to-end. We discuss affordances of parallel bargrams in the context of systems that support consumer-based information exploration and choice based on the attributes of the items in the choice set. Our tool called EZChooser has enabled a number of prototypes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 17 publications
(15 reference statements)
0
41
0
Order By: Relevance
“…Linear diagrams were introduced by Leibniz [3], with parallel bargrams [4] and double decker plots [5] being similar. Each set is represented as one or more horizontal line segments, with all sets drawn in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Linear diagrams were introduced by Leibniz [3], with parallel bargrams [4] and double decker plots [5] being similar. Each set is represented as one or more horizontal line segments, with all sets drawn in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel Bargrams (Wittenburg, Lanning, Heinrichs, & Stanton, 2001) and SimulSort (Hur & Yi, 2009) are examples of such variations. By sorting values in all columns, a user can see overall trends more easily without changing sorting orders.…”
Section: Tabular Visualizationsmentioning
confidence: 99%
“…Wittenburg et al (2001) reported that the participants selecting an item from a menu of multiple items generally preferred EZChooser, an implementation of Parallel Bargrams, over a spreadsheet application. Table Lens was also compared with S-PLUS in terms of exploratory data analysis (EDA) using the GOMS (Goals, Operators, Methods, and Selection rules) method (Pirolli & Rao, 1996).…”
Section: Evaluation Of Tabular Visualizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides presenting a visualization that clusters similar antennas, the system also affords users the opportunity to explore the tradeoffs between the antennas' numeric performance measures [2]. Each of the sliders in Figure 4 corresponds to one dimension in the performance vector.…”
Section: Figure 2 the Dispersion Processmentioning
confidence: 99%